Determining nursing manpower needed in a sample hospital - F Akbari; F Kokabi; Sh yousefian (Tehran University of Medical Sciences, 2011)
Background: Hospital is the most expensive part of a health system. Manpower is the mainly valuable factor in productivity and service delivery. Since personnel costs make up more than 60% of hospital costs, increasing productivity and efficiency of human resources are significant. The most important ways to increase utilization of this valuable resource is to standardize the quantity and composition of the human distribution. This study determined the standardizing of nurses resources in a sample hospital. Materials & Methods: The descriptive and cross-sectional study applied in 2008. Data of study collected by questionnaires and library studies by using descriptive statistics were analyzed. Sample of study is the private general hospital with 85 active beds, including gynecology, surgery, men and children, women, surgery, neonatal intensive care wards. Data collection tools were tables containing the number and composition of nurses and hospital performance indicators. After gathering data, it compared with the standards and recommendations were conducted. Using standard of job hours of nursing care required for each group of patients and protocols of Ministry of Health and Medical Education. Findings: The numbers of nursing staff in the hospital were 96 people, including 38 nurses, 16 assistance nurses and 42 aid nurses. The optimum numbers based on average annual bed occupancy in different sectors were: 94 nurses, including 60 nurses, 34 assistance nurses and aid nurses. Conclusion: A sample hospital uses healthcare workers as an aid nurses to assist in a wide range of patients' care. With regard to development of medical sciences and become more specialized nursing care industry and major changes in techniques and equipments, to move on from traditional invasive surgical procedures to non-invasive medical practices and the incidence of further complex cases, it will be effected to replace them with educated nurses to care of patients.